Great games, local rules the new great power contest in Central Asia - Cooley, Alexander, 1972- (New York ; Oxford : Oxford University Press, 2012)
Russia, the US, and China all see Central Asia as strategically important and have devoted extensive financial and human resources there. In this book, Alexander Cooley explores the dynamics of the new competition for influence over the region since 9/11.
Description based on online resource; title from PDF title page (viewed on July 16, 2012).
Includes bibliographical references and index.
Keywords: Asia, Central -- Foreign relations -- 1991-; Geopolitics -- Asia, Central; Asia, Central -- Strategic aspects; Asia, Central -- Foreign relations -- United States; United States -- Foreign relations -- Asia, Central; Asia, Central -- Foreign relations -- Russia (Federation); Russia (Federation) -- Foreign relations -- Asia, Central; Asia, Central -- Foreign relations -- China; China -- Foreign relations -- Asia, Central